Corneal crosslinking in a case with Axenfeld–Rieger syndrome and unilateral pellucid marginal degeneration - Koc, Mustafa (Ther Adv Ophthalmol, 2019)
A 31-year-old male patient presented with the complaint of progressive vision loss in his left eye. Slit-lamp examination showed posterior embryotoxon, iris hypoplasia, and iridocorneal adhesion in both eyes, corectopia in the right, and peripheral inferior thinning and ectasia in the left eye. Corneal topography showed slightly asymmetric bowtie pattern in the right eye and crab-claw pattern in the left eye. Topographic examination was compared with his previous topography. The comparison showed 1.6-D steepening of maximum keratometry (K(max)) and 22-µm decrease of thinnest corneal pachymetry. Corneal crosslinking treatment was performed on the left eye. At the postoperative 28-month follow-up visit, K(max) decreased from 54.1 to 53.0 D and corrected distance visual acuity improved to 20/20 with scleral lens. This is the first reported a case with Axenfeld–Rieger syndrome and pellucid marginal degeneration association. We suggest that corneal crosslinking can be useful for management of pellucid marginal degeneration and longer follow-up might be needed in order to corroborate the effectiveness of the corneal crosslinking procedure.